Conhecimento sobre espaço biológico periodontal no âmbito acadêmico : um estudo com graduandos de odontologia no Espírito Santo - Rosa, Karol Loureiro Cuzzuol da (2014)
The goal of this investigation was to evaluate the knowledge level of undergraduate dental students who have completed the course of Periodontics in the dental schools of Espírito Santo state, Brazil, on the biological width (BW) and the clinical consequences during restorative treatment. The sample was composed of 317 academics, being separated into two groups: Intermediate Group - Third and Fourthyear students and Senior Group - Fifth-year senior students. The survey was of analytical character and drawing and cross-sectional design. For data collection, two self-administered questionnaires (clinical and theoretical), were used containing objective questions about two different topics: diagnosis and treatment of the BW. Additionally there was a question about their career plans after graduation degree.The Senior Group showed better results than Intermediate Group, regarding the mean percentage of correct answers 57.9% total hits. Comparing these two questionnaires it was observed that 6.0% of participants linked the practice with the theory regarding the diagnosis of the invasion of BW. In addition to it, 7.6% of students made a parallel between BW violation and its treatment. By relating future career plans with the total of right answers, worst results were observed among those students that have plans to be dental specialist with an average score of 3.47±1.31 versus 4.14±1.68 (p=0.03). Although the senior students have shown higher number of correct answers than Intermediate Group, their results were below expectations. The worst results were observed in those students who were focused in their area of specialization during graduation. Therefore, a greater emphasis should be given to BW during graduation, since it is considered a basic and very important topic to the future daily clinical practice.